Left hemicolectomy and low anterior resection in colorectal cancer patients: Knight–griffen vs. transanal purse-string suture anastomosis with no-coil placement - Ammendola, Michele; Filice, Francesco; Battaglia, Caterina; Romano, Roberto; Manti, Francesco; Minici, Roberto; de'Angelis, Nicola; Memeo, Riccardo; Laganà, Domenico; Navarra, Giuseppe; Montemurro, Severino; Currò, Giuseppe (Frontiers in Surgery, 2023)
Background. Colorectal cancer (CRC) is considered as one of the most frequent neoplasm of the digestive tract with a high mortality rate. Left hemicolectomy (LC) and low anterior resection (LAR) with minimally invasive approach, laparoscopy (LS) and robotic, or with open technique are the gold standard curative treatment. Results. The patients were divided into two groups: the first with 39 patients who underwent LC and LAR in LS with Knight-Griffen anastomosis (Knight-Griffen group) and the second with 38 patients who underwent LC and LAR in open technique with Trans-Anal Purse-String Suture Anastomosis (TAPSSA group). Only one patient who underwent open technique had AL. POI was 3.76 ± 1.7 days in the TAPSSA group and 3.07± 1.3 days in the Knight-Griffen group. There were no statistically significant differences in terms of AL and POI between the two different groups. Conclusion. The important data that emerges preliminarily from this retrospective study is that the two different techniques were equivalent in terms of AL and POI, therefore all the advantages reported in the previous studies reported to the No-Coil, they can be applied regardless of the surgical technique used. Randomized controlled trials are needed to confirm these findings.